Perancangan Media Pembelajaran Animasi Pada Mata Pelajaran Pemrograman Web Materi “Konsep dan Implementasi Css” Menggunakan Aplikasi Online Powtoon di SMK Negeri 1 Tengaran - Michael Vandovi Theodora Delavega; Adriyanto Juliastomo Gundo (Peneliti.net, 2022)
The use of animation today is no longer a new thing in the education arena. Animated media is an audio-visual-based media, this learning media can present learning materials that are more interesting, not monotonous and facilitate the delivery of material. In learning activities Learning media is very important in the teaching and learning process, learning media is used as an intermediary. The selection of the right learning media can influence several factors, including: Learning Objectives, Learning Materials, Teaching Methods, and Learning Outcomes. Learning materials present a condition that can enable students to gain knowledge and skills (Kom, Kom, & Yuli Andika, 2022). The problem in this research is the discovery of students during the learning process having difficulty understanding the material presented by the teacher besides that students feel bored and lack the enthusiasm to learn when the teacher delivers material in the form of theoretical explanations.